Natural and Artificial Selection for Parasitoid Resistance in Drosophila melanogaster Leave Different Genetic Signatures - Gerritsma, Sylvia; Jalvingh, Kirsten M.; van de Beld, Carmen; Beerda, Jelmer; van de Zande, Louis; Vrieling, Klaas; Wertheim, Bregje (Frontiers in Genetics, 2019)
Adaptation of complex traits depends on standing genetic variation at multiple loci. The allelic variants that have positive fitness effects, however, can differ depending on the genetic background and the selective pressure. Previously, we interrogated the Drosophila melanogaster genome at the population level for polymorphic positions and identified 215 Single Nucleotide Polymorphisms (SNPs) that had significantly changed in frequency after experimental evolution for increased parasitoid resistance. In the current study, we follow up on 11 of these SNPs as putative targets of the experimental selection process (Jalvingh et al., 2014). We study the patterns of genetic variation for these SNPs in several European field populations. Furthermore, we associate the genetic variation of these SNPs to variation in resistance against the parasitoid Asobara tabida, by determining the individual phenotype and SNP genotype for 144 individuals from four Selection lines and four non-selected Control lines and for 400 individuals from 12 Field lines that differ in parasitoid resistance. For the Selection lines we additionally monitored the changes in allele frequencies throughout the five generations of experimental selection. For three genes, mbl (Zn-finger protein), mthl4 (G-protein coupled receptor) and CG17287 (protein-cysteine S-palmitoyltransferase) individual SNP genotypes were significantly associated with resistance level in the Selection and Control lines. Additionally, the minor allele in mbl and mthl4 were consistently and gradually favoured throughout the five generations of experimental evolution. However, none of these alleles did appear to be associated to high resistance in the Field lines. We suggest that, within field populations, selection for parasitoid resistance is a gradual process that involves co-adapted gene complexes. Fast artificial selection, however, enforces the sudden cumulating of particular alleles that confer high resistance (genetic sweep). We discuss our findings in the context of local adaptation.